Improvements in operant memory of Aplysia are correlated with age and specific gene expression - Randolph, Eric C.; Fieber, Lynne A. (Frontiers in Behavioral Neuroscience, 2023)
The transcription factor Aplysia CCAAT/enhancer binding protein (ApC/EBP) is expressed as an immediate early gene in the cAMP responsive element binding protein (CREB) mediated gene cascade, and it has essential functions in the synaptic consolidation of memory following a learning event. Synaptic consolidation primarily involves morphological changes at neuronal synapses, which are facilitated through the reorganization of the actin and microtubular cytoarchitecture of the cell. During early nervous system development, the transmembrane synaptic protein teneurin acts directly upon neuronal presynaptic microtubules and postsynaptic spectrin-based cytoskeletons to facilitate the creation of new synapses. It is reasonable to hypothesize that teneurin may also be linked to learning-induced synaptic changes and is a potential candidate to be a later gene expressed in the CREB-mediated gene cascade downstream of ApC/EBP. To assess the role of ApC/EBP and teneurin in learning and memory in the marine snail Aplysia californica, young (age 7-8 months) and aged (age 13-15 months; aging stage AII) siblings of Aplysia were trained in an operant conditioning paradigm-learning food is inedible (LFI)-over two days, during which Aplysia they learned to modify the feeding reflex. Aged Aplysia had enhanced performance of the LFI task on the second day than younger siblings, although far more aged animals were excluded from the analysis because of the initial failure in learning to recognize the inedible probe. After two days of training, ApC/EBP isoform X1 mRNA and teneurin mRNA were quantified in selected neurons of the buccal ganglia, the locus of neural circuits in LFI. Teneurin expression was elevated in aged Aplysia compared to young siblings regardless of training. ApC/EBP isoform X1 expression was significantly higher in untrained aged animals than in untrained young siblings but decreased in trained aged animals compared to untrained aged animals. Elevated levels of ApC/EBP isoform X1 and teneurin mRNA before training may have contributed to the enhancement of LFI performance in the aged animals that successfully learned.